2013
DOI: 10.1039/c3gc00090g
|View full text |Cite
|
Sign up to set email alerts
|

The electrocatalytic hydrogenation of furanic compounds in a continuous electrocatalytic membrane reactor

Abstract: The electrocatalytic hydrogenation of biomass derived oxygenates in a continuous electrocatalytic membrane reactor presents a promising method of fuel and chemical production that minimizes usage of solvents and has the potential to be powered using renewable electricity. In this paper we demonstrate the use of a continuous-flow electrocatalytic membrane reactor for the reduction of aqueous solutions of furfural into furfuryl alcohol (FA), tetrahydrofurfuryl alcohol (THFA), 2-methylfuran (MF) and 2-methyltetra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
146
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 126 publications
(147 citation statements)
references
References 51 publications
0
146
1
Order By: Relevance
“…According to previous reports, two reaction pathways for the ECH of FF exist as depicted in Scheme a: a direct and an indirect reaction for the production of MF from FF. The Li group showed direct conversion of FF to MF at low applied potential (−0.55 V vs. RHE) on Cu, having negligible conversion of FA to MF.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…According to previous reports, two reaction pathways for the ECH of FF exist as depicted in Scheme a: a direct and an indirect reaction for the production of MF from FF. The Li group showed direct conversion of FF to MF at low applied potential (−0.55 V vs. RHE) on Cu, having negligible conversion of FA to MF.…”
Section: Resultsmentioning
confidence: 95%
“…The standard redox potential (vs. reversible hydrogen electrode, RHE) for the HER is 0 V at pH 0. The standard redox potentials for the ECH of FF to FA, ECH of FA to MF, and ECH of FF to MF are +0.19 V, +0.13 V, and +0.31 V, respectively. This indicates that the ECH of FF is favored over the HER thermodynamically.…”
Section: Introductionmentioning
confidence: 99%
“…These are all key platform renewable non-petroleum based molecules [49,50]. Hydrogenation of furfuryl alcohol and furfural has been studied using Pt, Pd, and Ru catalysts [51][52][53][54][55]. Hydrogenation of carbohydrates (e.g., xylose to xylitol) is an industrial process using Ru catalysts [11].…”
Section: Catalyst Testingmentioning
confidence: 99%
“…[11] Recently,C hadderdon et al reported electrocatalytic oxidation of HMF on supportedg old and palladium bimetallic nanoparticles, showing that Pd 1 Au 2 /C oxidizes HMF selectively to FDCA with 83 %y ield in alkaline conditions (0.02 m HMF in 0.1 m KOH, 100 %c onversion in 1h,0 .9 V RHE ,2 58 C). [13] Green et al [14] also investigated furfural hydrogenation on aP d/C cathode catalysti napolymer electrolyte membrane (PEM) electrolyzer and reported that furfuryl alcohol with 54~100 %s electivity was obtained in water-based neutral pH. Similarly,f urfural (C 5 H 4 O 2 ), Electrocatalytic hydrogenation of 5-hydroxymethylfurfural (HMF) is studied on solid metal electrodes in acidic solution (0.5 m H 2 SO 4 )b yc orrelatingv oltammetry with on-line HPLC product analysis.…”
Section: Introductionmentioning
confidence: 99%